Online Store Atmosphere, Shopping Lifestyle, Emosi Positif Terhadap Impulse Buying Produk Wardah Pada E-Commerce - Nugroho, Arief Teguh; Ratnaningsih DS, Yunita Ramadhani; Praborini, Yuhaning (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
The purpose of this study was to determine the direct and indirect effects of online store atmosphere and shopping lifestyle on impulse buying decisions through positive emotions. Online store atmosphere and shopping lifestyle on impulse buying decisions through positive emotions. The population in this study were shopee marketplace users. Sampling using purposive sampling technique of 100 respondents. The data collection method used is a questionnaire. The analysis method in this study uses a structural model processed SMARTPLS 3.0 software. The results of this study indicate that the variables. Online store atmosphere and lifestyle have no significant effect on impulse buying, while positive emotions affect impulse buying, and shopping lifestyle affects positive emotions. While indirectly shopping lifestyle and positive emotions affect impulse buying. Suggestions for online stores should maximize attractive store arrangements so that consumers are encouraged to make impulse purchases.